Kecerdasan Buatan, Orisinalitas, dan Krisis Literasi: Disrupsi Teknologi Generatif dalam Transformasi Sastra Indonesia Kontemporer - Fradana, Ahmad Nurefendi; Suwarta, Nyoman (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
In the era of rapid digital transformation and global technological disruption, the contemporary Indonesian literature landscape is at a crossroads between innovation and preservation of cultural identity. This study investigates the impact of generative artificial intelligence (AI) on literary creativity, focusing on three core phenomena: the degradation of originality, an ethical literacy crisis, and the fragmentation of literary discourse. Utilizing a qualitative systematic literature review, the research analyzes digital literary corpora, educational policies, and public media discussions to explore how AI-generated content challenges traditional authorship and the intrinsic values of literature. Findings indicate that while AI technologies facilitate efficient production of texts, they often reproduce conventional patterns and diminish the unique human touch in creative works. Furthermore, the reliance on AI blurs the boundary between human and machine contribution, raising ethical concerns over accountability and the erosion of critical literacy skills. The study advocates for a hybrid model that integrates technological advancements with human creativity, proposing reforms in educational curricula and policy frameworks to safeguard ethical literary practices. The research provides a comprehensive insight into the transformative effects of AI in literature, emphasizing the need to balance innovation with the preservation of cultural and artistic authenticity in the digital age.